Seminal trace elements and their relationship with sperm parameters - Karabulut, Seda; Korkmaz, Serol; Güneş, Ertuğrul; Kabil, Erol; Keskin, İlknur; Usta, Melek; Omurtag, Gülden Zehra (Wiley, 2022)
Male reproductive problems may derive from many reasons including the environmental toxicants which may either intaken by occupational exposure, nutrition or bad air quality. The increased exposure to these substances due to rapid industrial development and technology has raised the questions: Is there a relationship between sperm parameters and these substances, and if so, in what extent? Results of studies on the subject reported conflicting results, many of which were not investigated in the seminal plasma. The aim of the current study was to evaluate the relationship between 23 metals and trace elements in human seminal plasma and semen parameters many of which were not investigated before. Levels of 23 metals in human seminal plasma were assessed by inductively coupled plasma mass spectrometry (ICP-MS). We examined the differences between subjects with normal ejaculate (normozoospermia) and pathologic ejaculate (with at least one abnormal semen parameter) according to the WHO criteria. The only significant difference was detected for Se while the other element's difference was not statistically significant. Se was statistically significantly increased in normal semen group suggesting the positive effect of this element on semen parameters.
Keywords: Seminal Plasma; Sperm; Trace Elements